2014
DOI: 10.1002/micr.22237
|View full text |Cite
|
Sign up to set email alerts
|

PDE-5 inhibition improves skin flap viability in rats that are exposed to nicotine

Abstract: PDE-5 inhibition exhibits a dose-dependent reduction in skin flap necrosis in rats exposed to nicotine. This suggests that PDE-5 inhibition may mitigate the ill effects of smoking on skin flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…1). Mauad et al 18 , Eskitascioglu and Gunay 40 , and Shah et al 8 also reported that nicotine administration decreases random flap survival rate to a range between 77.7% and 50.4%. These different percentages may be due to the difference in flap size, nicotine doses used, site of nicotine injection or species of the rats, but in general nicotine showed a deleterious effect on skin flaps.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1). Mauad et al 18 , Eskitascioglu and Gunay 40 , and Shah et al 8 also reported that nicotine administration decreases random flap survival rate to a range between 77.7% and 50.4%. These different percentages may be due to the difference in flap size, nicotine doses used, site of nicotine injection or species of the rats, but in general nicotine showed a deleterious effect on skin flaps.…”
Section: Discussionmentioning
confidence: 97%
“…Nicotine (Sigma Chemical, St Louis, MO, USA) was given at a dose of 4 mg/kg by daily SC injections in 1 ml normal saline for 40 days before surgery and 7 days after 18 . Nicotine was injected at the site of the base of the future flap 8 . SC injections were used for slower absorption rates to overcome the high toxicity of nicotine.…”
Section: Methodsmentioning
confidence: 99%
“…These observations are corroborated by preliminary laboratory results from our group demonstrating enhanced flap tissue survival after administration of sildenafil in the setting of nicotine exposure in a rodent flap model. 41 On the basis of these beneficial vascular and perfusion effects, we sought to investigate the role of PDE-5 inhibitor on a clinical series of tobacco cigarette smoker undergoing facial flap reconstruction with the hypothesis that PDE-5 inhibitors would reverse the damaged and suboptimal vascular environment present in a tobacco user's skin flap. Before administration of sildenafil, we paid critical attention to characteristics of robust flap design.…”
Section: Discussionmentioning
confidence: 99%
“…The drug inhibits PDE5, elevating the intracellular cGMP level, in turn increasing blood flow, triggering vasodilation, and inhibiting thrombus formation by virtue of an effect on platelets. Sildenafil has been used to increase the viable areas of randomly patterned flaps . Experimentally, sildenafil has been shown to protect against I/R injury .…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil has been used to increase the viable areas of randomly patterned flaps. 7,8,26 Experimentally, sildenafil has been shown to protect against I/R injury. 27 Gori et al 28 showed that sildenafil opens K ATP -sensitive channels, reducing I/R injury and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%